Impact of COVID-19 on Mental Health of Chinese Residents in Its Initial Stage - Yang, Linchuan; Liu, Yunhong; Han, Li; Ao, Yibin; Yang, Hongtai (Frontiers in Psychology, 2021)
This study aims to investigate the effect of coronavirus disease 2019 (COVID-19) on the Chinese public’s mental health during its early stage. We collected our data through an online questionnaire survey. Specifi-cally, we adopted the Impact of Event Scale-Revised (IES-R) and State-Trait Anxiety Inventory (STAI) to assess symptomatic responses to exposure to traumatic life events and public anxiety, respectively, in the COVID-19 pandemic outbreak. Then, we assessed the differences in the scores among various so-cio-demographic groups using Kruskal-Wakkis H tests and t-tests and analyzed the IES-R, SA, and TA scores using the Pearson correlation analysis. Finally, we conducted a path analysis to determine the mediation role of IES-R in the relationship between TA and SA. The results show that the average of the SA and TA scores were 48.0 ± 10.4 and 38.0 ± 8.2, respectively; the respondents who suffered from mild, moderate, and severe psychological impacts because of the health crisis accounted for 21.9%, 5.2%, and 13.1%, respectively; farmers have the highest IES-R score than other occupational groups; people with the highest income has the lowest SA level; a significant positive correlation existed between the IES-R and STAI scores; and TA pro-duces both direct and indirect (through IES-R) on SA. Overall, the general Chinese public exhibited much higher anxiety levels than normal in the early days of the pandemic outbreak. Accordingly, we highly rec-ommend psychological counseling and psychological intervention support to mitigate the adverse psycho-logical impacts of such an event.